PENGARUH PENYAKIT GIGI DAN MULUT TERHADAP HALITOSIS - Ni Putu Adnyani; I Made Budi Artawa (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Dental Health of include cover congeniality about healthy tooth, of caries other diseases and that happened in mouth cavity. Health of unfavorable mouth and tooth and diseases in mouth cavity which do not be taken care of, often represent trouble of feel generated pain as well as can generate to feel to lower self to its patient caused by mouth aroma which is not delicate or recognized with halitosis. Problems of this research do disease of mouth and tooth can generate halitosis. Intention of this research is to know role of disease of mouth and tooth to the happening of halitosis. This research of descriptive method, because only giving picture about an situation objectively. This research present theorys beforehand and studied problems answer pursuant to obtained theorys through bibliography study. Result of this research indicate that halitosis happened caused by plaque accumulation, poket, haemorrahage and deterioration of network at tooth caries, gangraen pulpa, gingivitis, periodontitis, stomatitis, glosistis, and oral cavity cancer. Conclude this research is halitosis happened caused by make-up of caused by VSC the existence of plaque stomachache, poket, haemorrahage and deterioration of network at tooth caries, gangraen pulva, gingivitis, periodontitis, stomatitis, oral cavity cancer and glositis. Suggested to society so that to be always keep in good health tooth and mouth so that protected from halitosis. To medical energy specially nurse of tooth of so that intensifying preventive program of disease of mouth and tooth to prevent incidence of halitosis